Editorial - Quadri, R. F. (POMLIF Journal of Library and Information Science, 2019)
The use of social media has helped to transform library service delivery as a number of studies have reported. Librarians and other professionals in the information world have continued to appreciate the importance of social media virtually in all things they do.